Evaluasi Daya Dukung Tanah Dasar Berdasarkan Nilai CBR Hasil Pengujian DCP pada Ruas Jalan Tikung–Kembangbahu Kabupaten Lamongan - Fadhlul Alimun Huda; Nur Indah Mukhoyyaroh; Ahmad Ridwan (Universitas Batanghari Jambi, 2026)
The Tikung–Kembangbahu road section in Lamongan Regency shows several indications of pavement distress; therefore, the bearing capacity of the subgrade needs to be evaluated as one of the bases for road treatment. This study aims to evaluate the subgrade bearing capacity based on the California Bearing Ratio (CBR) obtained from Dynamic Cone Penetrometer (DCP) testing. The test was conducted at five points with an interval of 200 m along a 1,000 m road section. The DCP penetration data were converted into CBR values, and the CBR values of the subgrade layer were used to determine the design CBR. The results show that the subgrade CBR values at the five test points were 12.8%, 3.23%, 3.3%, 8.42%, and 10.9%. The lowest CBR value of 3.23% was selected as the design CBR because the number of test points in one segment was less than ten. This value is lower than the minimum CBR requirement of 6%, indicating that subgrade improvement is required before pavement design. Based on the Bina Marga Pavement Design Manual, the recommended thickness of the subgrade improvement layer is 200 mm.